Pengaruh Keragaman Produk dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen di KKV Tunjungan Plaza Surabaya - Pratiwi, Meyria (Research Journal of Social Science and Economics, 2025)
This study aims to determine the effect of product diversity and product quality on consumer purchasing decisions at a store in Tunjungan Plaza Surabaya. The type of research used is quantitative with data collection through questionnaires distributed to respondents. The sampling method used is Accidental Sampling, where the sample is based on chance, that is, anyone who happens to meet the researcher can be used as a sample. The results showed that product diversity and product quality have a significant influence on consumer purchasing decisions. Product diversity variables, which include variations in product brands, variations in product completeness, variations in product size, variations in product quality, and variations in product design, have an important role in attracting consumer interest in buying. In addition, product quality is also a factor that influences consumer purchasing decisions. Product quality as measured from the aspects of durability, aesthetic value, product performance, and the benefits provided to consumers, has a significant influence on purchasing decisions. Consumers tend to choose products with good quality and can meet their needs. And it must also be tested to determine the effect of influential variables. This research contributes to understanding the importance of product diversity and product quality in the context of consumer purchasing decisions. The findings of this study can be used by retail companies to plan effective marketing strategies, including varied product development, consistency and improved product quality. Keywords: Product diversity, Product quality, Consumer purchasing decisions